The Effect of Profitability, Liquidity, and Solvency on Financial Distress of Textile and Garment Companies in Indonesia - Nathaniel Maximillian; Fanny Septina (LPPM Universitas BSI, 2022)
Indonesia's manufacturing GDP growth experienced a downward trend from 2015-2020. All manufacturing companies experienced a decline, including textile and garment sub-sector companies. There are 4 textile and garment sub-sector companies that have suffered consecutive losses and high raw material costs caused indications of financial distress in textile and garment sub-sector companies. This study aims to determine the effect of profitability, liquidity, and solvency on financial distress in textile and garment sub-sector companies for the period 2015-2020. Profitability is measured by Return On Asset (ROA), liquidity is measured by Current Asset (CR), solvency is measured by Debt to Asset (DAR), and financial distress is measured by Altman Z-score. This study sample used 15 textile and garment sub-sector companies listed on the Indonesia Stock Exchange. This study uses a quantitative approach. Data analysis method using Pooled Least Square. The results showed that profitability and liquidity had a positive and significant effect on financial distress. Solvency has a negative and significant effect on financial distress.